2008
DOI: 10.2174/1874846500801010042
|View full text |Cite
|
Sign up to set email alerts
|

Growth, HRXRD, Microhardness and Dielectric Studies on the NLO Material L-Alaninium Maleate

Abstract: The single crystals of the NLO material, L-Alaninium maleate were grown by using the submerged seed solution method. The identity of the crystal was confirmed by single crystal X-ray diffraction. The crystalline perfection was analyzed using high resolution X-ray diffraction and it was found that the crystalline perfection is quite good. The values of the laser damage threshold and the Vicker's microhardness are in the higher range. The dielectric studies at different temperatures showed that the dielectric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Laser damage threshold value for grown LTP crystal was measured using single shot laser pulses from Nd:YAG laser source with 10 ns pulse width and at 10 Hz repetition rate. [17][18][19] 2.2.5 Birefringence analysis. Optical homogeneity and birefringence of the crystal was evaluated using modied channel spectrum (MCS) experimental setup, which was based on the principle of channelled spectra.…”
Section: Characterization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser damage threshold value for grown LTP crystal was measured using single shot laser pulses from Nd:YAG laser source with 10 ns pulse width and at 10 Hz repetition rate. [17][18][19] 2.2.5 Birefringence analysis. Optical homogeneity and birefringence of the crystal was evaluated using modied channel spectrum (MCS) experimental setup, which was based on the principle of channelled spectra.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…The energy density was calculated using the formula E/A where E is the input energy and A is the area of circular spot. 17,18 The value obtained for 1 pulse per second is tabulated in Table 1. LTP was observed to possess reasonably high laser damage threshold value compared to other well-known organic and inorganic crystals, such as KDP and urea, used for NLO applications.…”
Section: Laser Damage Threshold Measurementmentioning
confidence: 99%
“…In the present study, the laser damage threshold (LDT) of the title compound has been determined by using a Nd:YAG laser having the wavelength of 1064 nm with 10 ns pulse width (FWHM) and at 10 Hz repetition rate. The energy density was calculated using the formula E/A (J cm 22 ), 13 where E is the input energy in millijoule (mJ) and A is the area of the circular spot. The laser damage density of ninhydrin was found to be 3.5 J cm 22 .…”
Section: Laser Damage Threshold Phase Matching Angle and Shg Measurem...mentioning
confidence: 99%
“…The inclusive optical characterstics of LA were described by L. Mosoguti et al, and the reported the modest SHG efficiency of LA, which was one-third of pure KDP crystal along with analogous hardness and thermal expansion to supplementary organic crystals [12]. Later, various researcher reported the growith of L-alanine tetrafluoroborate [13], L-alaninium oxalate complex [14], L-alanine acetate with the pH of 3.0 [15], L-alaninium maleate (LAM) with the size of 19 × 6 × 5 mm 3 with SHG efficiency 0.8 times that of KDP [16], L-alanine hydrochloride monohydrate with SHG value 1.3 times that of KDP [17]. Recently, 8-hydroxyquinolinedoped L-alanine components [18] were reported and proven the potentiality of LA in the mixed forms.…”
Section: Introductionmentioning
confidence: 96%